Environmental management practices in the manufacturing sector? Hungarian features in international comparison - Gábor Harangozó; Sándor Kerekes; Ágnes Zsóka (Journal for East European Management Studies, 2010)
The paper provides an overview of the state of corporate environmental management in Hungary compared to older EU and OECD states. It also explores the complex relationship between the implementation of environmental management practices and corporate environmental and business performance. Empirical evidence is taken from a comprehensive piece of research, carried out in OECD member countries, which explored motivation, decision-making procedures, and organisational structure of companies in relation to the design and implementation of environmental management tools and systems. – – Der Artikel bietet einen Überblick über die Situation des betrieblichen Umweltmanagements in Ungarn im Vergleich zu den älteren EU- und OECDLändern. Weiterhin werden die komplexen Beziehungen zwischen der Implementierung von Umweltmanagement-Praktiken und der betrieblichen Umwelt- und Geschäftsperformanz analysiert. Die empirische Evidenz basiert auf umfangreichen Forschungen in OECD-Mitgliedsländern, wobei insbesondere Motivation, Entscheidungsprozesse und Organisationsstruktur von Unternehmen im Zusammenhang mit Design und Implementation von Umweltmanagement-Instrumenten und -Systemen erforscht wurde.
Keywords: 650; environmental management; corporate environmental performance; EMS; stakeholder orientation; environmental function; environmental impact; environmental measures